Sequential Therapy of Community-Acquired Pneumonia in Children - I.A. Karimdzhanov; G.Kh. Iskanova; N.A. Israilova (Zaslavsky O.Yu., 2014)
Aim of the study - to examine the effectiveness of sequential therapy of injectable and oral forms cephalosporins of II generation, cefuroxime sodium and cefprozil, in children with acute community-acquired pneumonia. We examined 53 child patients aged 6 months - 14 years with acute community-acquired pneumonia. Patients were divided into 2 groups: 1st group - 26 patients who treated with cefuroxime sodium intramuscularly, and 2nd - 27 patients who treated with cefuroxime sodium in first 3 days and then from the 4th day - with cefprozil suspension orally. Both groups of patients were comparable by forms and course of pneumonia. In the clinic to all patients were conducted conventional clinical and laboratory investigations. Complex therapy was not different in both groups. Efficacy of treatment was assessed in dynamics. When comparing the effectiveness of two antibiotic regimens (cefuroxime sodium parenterally and sequential regimen with replacement by cefprozil orally) there were no differences in the dynamics of clinical course, laboratory and radiological data. Finding of the conducted investigations before treatment showed that majority of patients had clinical and radiological evidence of pneumonia: fever, cough, shortness of breath, tachycardia, physical and radiological changes in the lungs. Evaluation of treatment efficacy showed that by the end of treatment in both groups of patients there was a positive clinical and radiological dynamics of the disease, the body temperature returned to normal, symptoms of intoxication, physical changes in the lungs disappeared, focal and infiltrative changes disappeared completely. Thus, sequential therapy with cephalosporins of II generation, cefuroxime and cefprozil, in the treatment of acute community-acquired pneumonia in children is a quite effective and safe method with good tolerability and no side effects.